Global impacts of scientific publications by academic staff: a case study of College of Medical Sciences, University of Maiduguri, Nigeria - Mohammed Bukar; Sulayman T. Balogun; Adewale L. Oyeyemi; Abdullahi A. Bukar; Medugu J. Thomas (Ntec Specialist, 2022)
Background: The impacts of scientific research by an individual or institution are measured using various bibliometric indices such as the h-index and citations index among others. Objective: The present study assessed the global impacts of scientific publications by academic staff of the College of Medical Sciences, University of Maiduguri (CMS-UNIMAID) using selected bibliometric indices. Methodology: The data (demographic data, research experience, and the number of publications) of the 202 academic staff of CMSUNIMAID were obtained from the records submitted for the 2019/2020 annual appraisal. The h-index, citations index (CI), number of documents (ND), RG score, research interest (RI), citation/item, and citation/year of the staff were extracted from Google Scholar, Publons, ResearchGate, and Scopus using authors search until 25th December 2020. Staff and publication online visibilities were determined. Descriptive statistics were prepared for all records obtained and subjected to appropriate inferential statistics. Results: The mean age and research experience of the staff were 45.4±9.2 and 13.9±9.6 years, respectively. The majority (p less than 0.05) of the staff were male (85.1%), had a PhD/Professional Fellowship (61.4%), and were senior academic staff (53.5%). A total of 4940 publication entries were submitted for the appraisal. Only 2.5% of the staff were visible on all platforms with staff online visibility of 63.9, 55.5, 15.8, and 5.0% (p less than 0.05) on Scopus, ResearchGate, Google Scholar, and Publons, respectively. Male staff (68.0%) were more visible (p less than 0.05) than their female counterparts (40.0%) on Scopus while senior academic staff were more visible (p less than 0.05) than junior academic staff on all platforms except Publons. Publication online visibility was highest (p less than 0.05) in Google Scholar (78.4%) and ResearchGate (65.9%) than Publons (28.0%) and Scopus (25.1%). The mean h-index, CI, and ND were 8.3±1.1, 401.8±97.8, and 36.2±4.9, respectively on Google Scholar and 5.0±0.4, 166.4±25.6 and 9.0±0.9, on ResearchGate. Publons showed means h-index, CI, and ND of 5.0±0.3, 77.2±13.7, and 25.6±2.1, respectively while Scopus showed 4.0±1.6, 144.4±95.3, and 14.5±6.2, respectively. In addition, the means RG score and RI were 10.0±0.7 and 113.1±15.4, respectively while the means citation/item and citation/year were 3.9±1.7 and 10.7±6.8, respectively. Conclusions: Low bibliometric indices indicate poor global impact of scientific publications from CMS-UNIMAID. Concerted efforts are required to improve the quality of research and publication through adequate funding, infrastructure, and mentorship among others.